Contribution to clinical study and nosographic Carrion's disease - Bernales, Sergio E. (1939)
It is a contribution to the clinical study and nosographic Lobstein's disease, the study of some cases of the disease, the first listed in the country. These cases are almost all families in which members have found that the disease Lobstein, which as is known, is considered family and inherited disease.